Giant siliconoma mimicking locally advanced breast cancer: A case report and review of literature. (2018) - Carson, Bryce; Cox, Steven; Ismael, Hishaam
Highlights: Siliconomas of the breast develop as a result of implant rupture and present with many of the signs and symptoms of breast cancer. MRI is the preferred study for diagnosis and a preoperative tissue sample should be attempted. We present a patient with a giant breast siliconoma and perform a comprehensive literature review. Our patient underwent a modified radical mastectomy with delayed closure. The majority of patients should undergo surgery due to symptoms or the inability to rule out cancer. Abstract: Introduction: Silicone prosthetics are widely used for breast augmentation and reconstruction. These devices may extrude free silicone into surrounding tissue, stimulating a granulomatous foreign body reaction. The resulting mass can mimic breast cancer. Presentation of Case: 71 year old female with a history of a ruptured silicone implant presents with an enlarging left breast mass. Exam demonstrated and ulcerated, fungating mass with active infection. CT scan demonstrated a 23 × 15 cm mass involving the breast and chest wall with axillary lymphadenopathy. Preoperative biopsies were inconclusive and the patient underwent a modified radical mastectomy. Pathology demonstrated a siliconoma. Discussion: While benign, silicone granulomas of the breast can present similarly to malignancy and are an important differential in the diagnosis of a breast or axillary mass for appropriate patients. MRI is the study of choice and core needle biopsies cannot always establish the diagnosis preoperatively. PET scans can be falsely positive and the diagnosis requires an extensive workup to rule out cancer. Conclusion: Siliconomas develop as a result of implant rupture and present with many of the signs and symptoms of breast cancer. The majority of patients should undergo surgery for symptom relief or to rule out cancer.